(untitled) (Research, Society and Development, 2024)
Objective: To research, through literature review, the use of homeopathy as an alternative treatment for many pathologies involved in ​​dentistry field. Methodology: online searches using databases available at PUBMED Central and VHL/BIREME. Other platforms such as Web of Science, Science Direct and Google Academy. Results: Our search resulted in 25 articles. Conclusion: Despite the mysticism that surrounds it, the use of homeopathic medicines in dental treatments is, in fact, a scientifically proven alternative treatment, which helps in various pre and post surgical procedures, which has a low financial cost and great effectiveness, enabling a contribution to dental care. Scientific study in this area requires more research and clinical evidence, so that this practice is more widespread and used by dental surgeons, in addition to the application of homeopathy as a discipline in dentistry.